SOSIALISASI SARANA SANITASI DAN POLA HIDUP SEHAT DI DESA BAHAGIA PADA MASA PANDEMI COVID-19 - Eren Pramestia Dewi; Ainur Rofieq; Adi Susila (An-Nizam, 2022)
A good living environment can support a healthy community life. Activities to assess this situation by carrying out environmental sanitation assessments with aspects related to several things such as the availability of clean water, sanitation for waste disposal, the physical condition of buildings, air quality, as well as other conditions such as transportation facilities, and the availability of social services. This community service is a form of application of the third Tri Dharma of Higher Education. The method used in community service is carried out by observation, socialization, data collection and mentoring/evaluation. The material presented in this socialization was general knowledge about sanitation facilities and healthy lifestyles during the Covid-19 pandemic. The purpose of holding this activity is to increase knowledge and awareness about the importance of sanitation facilities and a good healthy lifestyle for prevention during the Covid-19 pandemic, provide several theories and general descriptions of the usefulness of good sanitation facilities developed in daily life and sustainable lifestyles. clean and healthy which should be made a habit in the community, especially the place to live, disseminating information conveyed to family, relatives, friends so that the knowledge gained can be absorbed and spread widely and apply it in everyday life. The benefits of this program activity are that the community can apply hygiene in household sanitation, educate and provide comfort for the people around us. Always reminding each other how important health is, starting from the household environment, maintaining cleanliness in every home, conducting community associations for healthy and clean environments such as waste banks, mutual cooperation, and community service.